Analysis of Government Policies in Structuring State Owned Corporation Through The Formation of Holding Companies - Ahmad Ishak; Aminuddin Ilmar; Winner Sitorus (Jurnal Hukum Volkgeist, 2021)
The legality of establishing a BUMN holding company is only based on Government Regulation Number 72 of 2016 concerning procedures for Equity Participation and Administration of State Capital in BUMN and Limited Liability Company, as an amendment to Government Regulation Number 44 of 2005 has not been fully comply with the principle of coherence with the above regulations namely Law Number 17 of 2003 concerning State Finance, Law Number 19 of 2003 concerning BUMN and Law Number 40 of 2007 concerning Limited Liability Companies. The purpose of this study is to find a concept of regulation and supervision the government on SOEs related to holding companies This research is normative with a statute approach and a conceptual approach. The results in this study are the need for legal reconstruction in BUMN where a law is needed that is central to regulate holding companies in Indonesia, where this law was born to provide related guidelines a mechanism for the formation, selection of the type of holding, and governance of State-Owned Enterprises in the form of Holding Company. The form of supervision on the implementation of BUMN holding in the future can be an integrated monitoring pattern is applied. In this supervision, 3 parties must be involved in a coordinated manner, namely the Parent Company Commissioner, the Supreme Audit Agency (BPK), and the Ministry of SOEs.